Proposed new interior design of extreme shop at 2-16, Festival Walk, Jln Medan Ipoh, 31400 Ipoh, Perak for Extreme Garment Sdn Bhd / Muhammad Taufiq Aziz - Aziz, Muhammad Taufiq (2012)
This project is about proposed new interior design of Extreme Shop at Festival Walk Ipoh for the Extreme Garment Sdn Bhd. Creativity and intellectuality is the important element to developt this project especially on design. The design process is base on the ganeral issue and design issue. Festival walk, Ipoh has been choosen as a new site for the new branch of Extreme Shop. There are many potantial for this site. Perak states also are non family in tourism industrial as they declared for 2012 is the Visit Perak Year. This project also defend their element, design will be related on their element and style. Not only the design, this project also give a confirtable on retail services especially for the customer.